Repercussions of remote learning in Nursing Education in the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: to reflect upon distance learning in the process of educational development in Nursing in the context of the COVID-19 pandemic. Methodology: a reflexive article which has as its central axis the COVID-19 pandemic and distance learning (EaD in Portuguese), and the educational development of nurses, focusing on three theoretical sections: i) Distance education: brief contextualisation, advantages and disadvantages, ii) The education of nurses in the context of distance education: criticism, challenges and implications, iii) Repercussions of the coronavirus pandemic in the educational process of nurses. Results: Nursing has as its main focus the caring of others and the Bachelor of Science in Nursing seeks to enable professionals to carry out planning, organising and supervising activities as well as implementing and providing clients and communities with special care. In spite of the effort to implement distance education, as a consequence of the pandemic, it is noticeable that in the context of the field of Nursing such fact leads to losses in the teaching-learning process. Concluding remarks: The Bachelor of Science in Nursing aims to assist professionals in being capable of performing duties in the healthcare industry, which presupposes the need of praxis for the development of technical, relational and managerial abilities. Therefore, there are considerable limits to be taken into consideration in this pandemic context as far as the educational development of nurses is concerned.